Calcification Moderates the Increased Susceptibility to UV Radiation of the Coccolithophorid Gephryocapsa oceanica Grown under Elevated CO2 Concentration: Evidence Based on Calcified and Non‐calcified Cells. (8th June 2018) - Miao, Hangbin; Beardall, John; Gao, Kunshan
Abstract: The physiological performance of calcified and non‐calcified cells of Gephyrocapsa oceanica (NIES‐1318) and their short‐term responses to UV radiation were compared for cultures grown under present‐day (LC, 400 μatm) and high pCO2 (HC, 1000 μatm) conditions. Similar growth rates and F v / F m values were observed in both types of cell under LC conditions, indicating that the loss of calcification in the non‐calcified cells did not lead to a competitive disadvantage under such conditions. Detrimental effects of elevated pCO2 were observed in both cell types, with the growth rate of non‐calcified cells decreasing more markedly, which might reflect a negative impact of higher cytoplasmic H + . When exposed to short‐term UV radiation, similar trends in effective quantum yield were observed in both cell types acclimated to LC conditions. Elevated pCO2 and associated seawater chemical changes strongly reduced effective quantum yield in non‐calcified cells but no significant influence was observed in calcified cells. Based on these findings and comparisons with previous studies, we suggest that the negative impact of elevated cytoplasmic H + would exacerbate the detrimental effects of UV radiation while the possession of calcification attenuated this influence. Abstract : Time course of changes in effective quantum yield (a, b, c, d) and the yield ratio (HC/LC) (e, f) of N and C cells grown under LC (400 μatm CO2 ) or HC (1000 μatm CO2 ) conditions while exposed to a solar radiation simulator under P, PA and PAB treatments. The vertical lines indicate SD ( n = 3).